CO2/CH4 and O2/N2 kinetic selectivities of oil palm shell-based carbon molecular sieves - Ahmad, M.A.; Daud, Wan Mohd Ashri Wan; Aroua, Mohamed Kheireddine (Malaysian Palm Oil Board, 2008)
Carbon molecular sieves (CMS) have become an interesting area of adsorption due to their micro porous nature and favourable separation factor on size and shape selectivity basis for many gaseous systems. In this work, CMS were prepared from locally available oil palm shell by thermal treatment of carbonization followed by steam activation, then benzene deposition. The carbonization of dried palm shell at 900 Cfor 1 hr followed by steam activation at 30-420 mm produced activated carbons with various degrees of burn-off. The highest micropore surface area and micropore volume of the activated samples were obtained at 53.2 burn-off. This sample was found suitable to he used as precursor for CMSs production in the deposition step. Subsequent henzene deposition onto activated samples at temperatures from 600C-900C for various henzene concentrations resulted in a series of CMS with different 02/N2 and C02/CH4 kinetic selectivities.